2014
DOI: 10.7731/kifse.2014.28.6.076
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Tidal Volume and Airway Pressure with a Bag-valve Mask using RespiTrainer

Abstract: The purpose of this study was to comparative analysis of tidal volume and airway pressure after one-rescuer BVM, two-rescuer BVM, advanced airway devices with a Bag-valve mask using RespiTrainer. The data were obtained from June 2 to 10 in 2014. The collected data were analyzed using the SPSS WIN 18.0 program. The results showed that BVM ventilation using the endotracheal intubation produced higher mean tidal volume 497 ± 78 mL, Two-rescuer ventilation 479 ± 91 mL One-rescuer ventilation 386 ± 59 mL, King LTS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
3
2
Order By: Relevance
“…The PP is the maximum pressure applied to the lungs during one round of ventilation, and a previous study reported that the maximum allowable range of PP that does not cause adverse effects is ≤40 cmH 2 O [ 21 ]. In this study, the average PP was 15.56 cmH 2 O, which was higher than the pressure applied by Uhm and Kim (11.62 cmH 2 O) [ 21 ] and Shin et al (8.71 cmH 2 O) [ 18 ]. Based on the method used in a previous study [ 23 ], the PP that was applied in this study was within the optimal level range for the prevention of adverse effects.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The PP is the maximum pressure applied to the lungs during one round of ventilation, and a previous study reported that the maximum allowable range of PP that does not cause adverse effects is ≤40 cmH 2 O [ 21 ]. In this study, the average PP was 15.56 cmH 2 O, which was higher than the pressure applied by Uhm and Kim (11.62 cmH 2 O) [ 21 ] and Shin et al (8.71 cmH 2 O) [ 18 ]. Based on the method used in a previous study [ 23 ], the PP that was applied in this study was within the optimal level range for the prevention of adverse effects.…”
Section: Discussioncontrasting
confidence: 62%
“…The data such as Vt and PP were delivered to the PDA via Bluetooth and calculated automatically. The Quick Lung ® was set at a compliance of 50 mL/cmH 2 O and a resistance of 5 cmH 2 O/L⋅s according to the methods used in previous studies [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…A previous study (25) reported that PP > 20 cmH2O resulted in adverse effects such as gastric insu ation. In this study, the average PP was 11.62 cmH2O, lower than that from a previous study (13); however, this was higher than the 8.71 cmH2O previously reported (17). PP is directly proportional to TV; low PP was associated with suboptimal TV (321.6 mL) in this study.…”
Section: Discussioncontrasting
confidence: 79%
“…A Quick Lung® (IngMar Medical) and personal digital assistance were connected to the manikin, and data were sent to the personal digital assistance through its embedded device. The Quick Lung® was set with compliance of 50 mL⋅cmH 2 O − 1 and resistance of 5 cmH 2 O⋅L − 1 ⋅s based on previous studies (17,18). Participants were instructed to use a BVM (1600 mL, Ambu Mark -Reusable Resuscitator with silicon face mask size 5; Ambu, Copenhagen, Denmark) to ventilate the manikin, simulating an adult with respiratory arrest, for two minutes (measured using a metronome (10 times/min)).…”
Section: Experimental Environment Tv and Ppmentioning
confidence: 99%
“…A Quick Lung® (IngMar Medical) and personal digital assistant were connected to the manikin, and data were sent to the personal digital assistant through its embedded device. The Quick Lung® was set with compliance of 50 mL·cmH 2 O − 1 and resistance of 5 cmH 2 O·L − 1 ·s based on previous studies [ 19 , 20 ]. Participants were instructed to use a BVM (1600 mL, Ambu Mark IV- Reusable Resuscitator with silicon face mask size 5; Ambu, Copenhagen, Denmark) to ventilate the manikin, simulating an adult with respiratory arrest, for 2 min (measured using a metronome (10 times/min)).…”
Section: Methodsmentioning
confidence: 99%